Diversity as strategic opportunity : exploring new paths to good administration - Simonati, Anna (Ethics in practice (Greenwich, Conn.), 2024)
"The principle of equality has always been considered as one of the fundamental values of modern societies; it compels administration to provide equal treatment to all subjects it enters in touch with, which is normally expressed as a general prohibition of discrimination. However, in recent times, the idea, according to which equality is not based only on protection against discrimination but also on promotion of diversity as a source of richness for society, is widely shared. This book gives a multidisciplinary overview of some of the possible methods and tools which are nowadays experimented by administration, in order to properly face the practical problems connected to diversity"--